2002
DOI: 10.1017/s1481803500007715
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic parameters of CK–MB and myoglobin related to chest pain duration

Abstract: ABSTRACT:Objective:Cardiac marker sensitivity depends on chest pain duration at the time of sampling. Our objective was to estimate the sensitivity, specificity, and likelihood ratios of early CK–MB and myoglobin assays in patients presenting to the emergency department (ED) with nondiagnostic ECGs, stratified by the duration of ongoing chest pain at the time of ED assessment.Methods:This was a prospective observational study carried out in 10 US and 2 Canadian EDs. Patients >25 years of age with ongoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…When patients arrive in the ED with chest pain, necrosis markers like CK MB and troponin have poor sensitivity, ranging from 28%-76% depending on the duration of chest pain. 7 Ischemia modified albumin may have better early sensitivity, ranging from 70%-92% depending on the test cut-off used; unfortunately, IMA has very poor specificity, generating a high proportion of false-positive results. [8][9][10][11] Worster and colleagues found that an IMA assay drawn at the time of patient presentation was 70% sensitive and 24% specific for serious cardiac outcomes.…”
Section: Sensitivity Specificity and Accuracymentioning
confidence: 99%
“…When patients arrive in the ED with chest pain, necrosis markers like CK MB and troponin have poor sensitivity, ranging from 28%-76% depending on the duration of chest pain. 7 Ischemia modified albumin may have better early sensitivity, ranging from 70%-92% depending on the test cut-off used; unfortunately, IMA has very poor specificity, generating a high proportion of false-positive results. [8][9][10][11] Worster and colleagues found that an IMA assay drawn at the time of patient presentation was 70% sensitive and 24% specific for serious cardiac outcomes.…”
Section: Sensitivity Specificity and Accuracymentioning
confidence: 99%